Qualitative Characters of Indigenous Sheep in Central Brazil: Putting Phenotype into Perspective - Allana Novais Aranda (MDPI AG, 2021)
For centuries, indigenous sheep have been bred in extensive low-input systems in Midwestern Brazil. The hypothesis of this study was the assumption that phenotypic evaluation of indigenous livestock may drive the establishment of breed standards and official breed recognition, and, therefore, promote more local business opportunities. On the basis of more integrative and participatory theoretical background to applying any decision based on phenotype, we designed this research to determine the most typical and unusual phenotypes of Pantaneiro sheep. Pantaneiro ewes (281 ewes from five conservation units in five counties) were evaluated, bearing in mind both conservation and development. Descriptive statistics were used to classify ewes into typical, intermediate, and unusual phenotypes. Chi-squared tests for association were performed to test if morphological variation in the different sampling sites occurred randomly (p > 0.05) or not (p < 0.05). Some results suggest some sort of diversifying selection pressure, i.e., distinct preferences among keepers. We observed considerable morphologic variation among ewes, but it was straightforward to determine the predominant phenotypes. The study evokes integrative agrobiodiversity by putting phenotypical characterization of indigenous livestock into perspective. Discussions coming from this study may support innovative governance and participative decision-making, allied with strategies that value the socioeconomic, biocultural, and adaptive aspects of indigenous livestock in tropical regions and developing countries. This is a challenge for government, rare-breed keepers, value-chain actors, and civil society.